2016
DOI: 10.1002/2015jb012211
|View full text |Cite
|
Sign up to set email alerts
|

Precise measurements of enthalpy of postspinel transition in Mg2SiO4 and application to the phase boundary calculation

Abstract: Drop solution enthalpies (ΔH°d‐s) of Mg2SiO4 ringwoodite, Mg2SiO4 forsterite, perovskite‐type MgSiO3 (bridgmanite), and MgSiO3 enstatite were measured using a single batch of 2PbO · B2O3 solvent at 978 K. From the obtained ΔH°d‐s values of Mg2SiO4 ringwoodite, MgSiO3 bridgmanite, and MgO, an enthalpy of the postspinel phase transition, Mg2SiO4 ringwoodite = MgSiO3 bridgmanite + MgO, was determined to be 78.54 ± 2.28 kJ/mol. Thermodynamic calculations using the obtained phase transition enthalpy and available t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 71 publications
(314 reference statements)
3
9
0
1
Order By: Relevance
“…The ab initio phase boundary is localized at slightly higher pressures (≈1-2 GPa) than those determined by other HP-HT experiments [124,127,129,130,133] (see Figure 11a). The calculated Clapeyron slope (i.e., dP/dT = −2.53 MPa/K) agrees well with those obtained by the most part of experimental investigations (ranging from −4.0 to −2.0 MPa/K) [121,[124][125][126][127]131,132,135], while other works [129,130,133,134] suggest a more gentle slope of the phase boundary (i.e., between −2.0 and −1.0 MPa/K or even less) (see Table 5). B3LYP results are in qualitative agreement with previous GGA calculations [137][138][139], whereas LDA [137] severely underestimates transformation pressures of the post-spinel reaction (see Figure 11b).…”
Section: Phase Equilibrium Calculation At Hp-ht: the Post-spinel Phassupporting
confidence: 75%
See 3 more Smart Citations
“…The ab initio phase boundary is localized at slightly higher pressures (≈1-2 GPa) than those determined by other HP-HT experiments [124,127,129,130,133] (see Figure 11a). The calculated Clapeyron slope (i.e., dP/dT = −2.53 MPa/K) agrees well with those obtained by the most part of experimental investigations (ranging from −4.0 to −2.0 MPa/K) [121,[124][125][126][127]131,132,135], while other works [129,130,133,134] suggest a more gentle slope of the phase boundary (i.e., between −2.0 and −1.0 MPa/K or even less) (see Table 5). B3LYP results are in qualitative agreement with previous GGA calculations [137][138][139], whereas LDA [137] severely underestimates transformation pressures of the post-spinel reaction (see Figure 11b).…”
Section: Phase Equilibrium Calculation At Hp-ht: the Post-spinel Phassupporting
confidence: 75%
“…Ab initio B3LYP results show an excellent agreement with the in situ LH-DAC X-ray diffraction study of Shim et al [128] and the multi-anvil experiments of Ishii et al [132], as well as with calculations based on accurate calorimetric measurements by Akaogi and Ito [126] and Akaogi et al [131] (Figure 11a; see also Figure Table 5), although a recent study found a lower enthalpy of reaction [134]. The ab initio phase boundary is localized at slightly higher pressures (≈1-2 GPa) than those determined by other HP-HT experiments [124,127,129,130,133] (see Figure 11a).…”
Section: Phase Equilibrium Calculation At Hp-ht: the Post-spinel Phassupporting
confidence: 71%
See 2 more Smart Citations
“…However, in applications where ab initio calculations are not possible, practical, or necessary, the simpler models are still being used. For example, Kojitani et al (2015) used the model in Kieffer (1979c) to estimate heat capacities for MgSiO 3 (bridgmanite) in calculations of the postspinel phase boundary in Mg 2 SiO 4 . Gavrikov et al (2015) and Gavrichev et al (2015) used the methodology to smooth measured data for new structural complexes in the lanthanide acetylacetonates and for samarium-monazite (SmPO 4 ) in the context of properties of pegmatites and granites.…”
Section: Related Resourcesmentioning
confidence: 99%